Examining operational wastes within Greek banking operations - Allen, Robby A.; Panagoulis, Giannis; White, Gareth R. T. (Emerald, 2019)
In order to address operational effectiveness in the banking sector caused by the 2008 global economic crisis, this study examines the nature of operational wastes that exist within four large Greek banks. A Delphi study was undertaken with ten managers and ten employees. The waste of underutilised people is found to be the dominant form of waste present and affecting the efficiency of banking operations. This has implications for managers of banking operations needing to address efficiencies in an increasingly competitive global economic environment. The paper also highlights the drawbacks of analysing typologies of waste across organisations and industrial sectors.